COVID-19 and persistent symptoms: implications for polycystic ovary syndrome and its management - Zhang, Shanshan; Wu, Yanqun; Mprah, Richard; Wang, Mingming (Frontiers in Endocrinology, 2024)
The COVID-19 pandemic has left a profound mark on global health, leading to substantial morbidity and mortality worldwide. Beyond the immediate symptoms of infection, the emergence of “long COVID”, the long-term effects of SARS-CoV-2, has become a significant public health concern. Long COVID is a multifaceted condition affecting various organs and systems, including the cardiovascular, digestive, nervous, and endocrine systems. Individuals diagnosed with polycystic ovary syndrome (PCOS) may face an increased risk of severe COVID-19 symptoms and infection. It is crucial to comprehend how long COVID affects PCOS patients to devise effective treatment and care strategies. Here, we review the detrimental effects of COVID-19 and its long-term effects on reproductive health, endocrine function, inflammation, metabolism, cardiovascular health, body composition, lifestyle, and mental health in patients with PCOS. We offer recommendations for the post-covid-19 management of PCOS, emphasizing the necessity of a comprehensive, multidisciplinary approach to patient care. Furthermore, we discuss prospective research directions, highlighting the significance of continued investigations and clinical trials to evaluate treatment approaches for long COVID and its ramifications in individuals with PCOS.